PENGARUH PROFITABILITAS, LEVERAGE DAN KEPEMILIKAN INSTITUSIONAL TERHADAP TAX AVOIDANCE - Humam Bimantoro Jati; Tyas Pambudi Raharjo; Marieta Ariani (Bajang Institute, 2025)
The Influence of Profitability, Leverage, and Institutional Ownership on Tax Avoidance (An Empirical Study on Property and Real Estate Companies Listed on the Indonesia Stock Exchange (IDX) for the Years 2020-2023). The purpose of this research is to analyze the influence of profitability, leverage, and institutional ownership on tax avoidance. This research method uses quantitative research methods, with types and data sources, namely secondary data obtained from the company's annual financial statements. company's annual financial report. The population and sample of this study are financial statements property and real estate companies listed on the Indonesia Stock Exchange in 2020-2023. The sampling technique used is purposive sampling, resulting in 112 processed data samples that meet the criteria. The analysis methods used are descriptive statistical tests, classical assumption tests, and hypothesis tests (bootstrapping). The results of this study indicate that profitability has effect on tax avoidance, leverage has no positive effect on tax avoidance, and institutional ownership has a positive effect on tax avoidance